Uterine Serous Carcinoma Arising From Endometrial Polyp: A Case Report - Sibel Bektaş; Burak Bahadır; Figen Barut; Ülkü Bayar; Şükrü Oğuz Özdamar (Medical Network, 2009)
Serous carcinoma is the prototype of type II endometrial carcinoma. A 71-year-old woman who had history of smoking, diabetes mellitus and hypertension admitted to the hospital with postmenopausal uterine bleeding. Curettage material was diagnosed as adenocarcinoma. Hysterectomy specimen revealed a uterine polypoid mass which afterwards was histopathologically proven to be a serous carcinoma arising from an endometrial polyp. Immunohistochemically, tumor cells showed diffuse reaction for p53 and c-erbB-2, and focal reaction for estrogen and progesterone receptors. In addition to history of diabetes mellitus and hypertension, our case shared some clinical and immunohistochemical characteristics of type I endometrial carcinoma, such as focal expression of estrogen and progesterone receptors. Overexpressions of p53 and c-erbB-2 in this tumor type should be considered.